An African Hermeneutics Re-Reading of Luke 18:1-8 and its Implications for Social Justice in Angola - Nelson Samaria (African Theological Journal for Church and Society)
Social inequality was a great concern in the context in which Jesus told the parable traditionally known as “the parable of the Unjust Judge and the Persistent Widow.” Jesus’s society was clearly marked by socio-economic and cultural imbalances between different social groups under the Roman rule. This was a common characteristic for all societies in the ancient Mediterranean world. Social injustice is also one of the greatest contemporary issues in Angola where the vast majority of the population have been living in extreme poverty for decades. The history of reception regarding the interpretation of this parable shows that for centuries it has been interpreted as an allegory or a metaphor of prayer and divine response, and very little attention is given to the issue of injustice. This article aims to highlight the implication of re-reading this parable in the Angolan context through the African hermeneutics lens with a liberation perspective. It also seeks to unveil the liberationist-educational function of the parable, identifying a Lukan model for social justice in the Angolan context.